Literasi Keuangan, Modal Usaha, Dan Pemanfaatan Media Sosial Terhadap Keberlanjutan Usaha Mikro Mahasiswa Young Entrepreneur Association Fakultas Ekonomi - Sintya Arviani; Luh Gede Kusuma Dewi; Putu Riesty Masdiantini (Universitas Pendidikan Ganesha, 2026)
The sustainability of micro businesses among students is still a problem, as evidenced by businesses that are unable to survive due to poor financial management, limited capital, and inadequate use of technology. This study aims to determine the influence of financial literacy, business capital, and social media utilization on the sustainability of micro-enterprises among students of the Young Entrepreneur Association, Faculty of Economics, Ganesha University of Education. The study used a quantitative approach with a binary logistic regression analysis method because the dependent variable was dichotomous, namely active and inactive businesses, with model validity tested using the Hosmer and Lemeshow test and parameter significance tested using the Wald test. The population in this study consisted of 47 student entrepreneurs, with a full sample obtained through a saturated sampling technique. Data were collected through questionnaires and analyzed using the SPSS program. The results of the study showed that (1) Financial literacy has a positive and significant effect on the sustainability of student micro-enterprises, (2) business capital has a positive and significant effect on the sustainability of student micro-enterprises, and (3) social media utilization has a positive and significant effect on the sustainability of student micro-enterprises. The study’s conclusions show that the sustainability of micro-enterprises among students is influenced by financial management capabilities, adequate capital, and optimal use of social media. Therefore, student entrepreneurs are expected to improve their financial literacy, manage their capital effectively, and optimize the use of social media to support business sustainability.